2011
DOI: 10.1021/nl103951e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered Surfaces Enhance Drug Loading and Adhesion

Abstract: To circumvent the barriers encountered by macromolecules at the gastrointestinal mucosa, sufficient therapeutic must be delivered in close proximity to cells 1 . Previously, we have shown that silicon nanowires penetrate the mucous layer and adhere directly to cells under high shear 2 . In this work, we characterize potential reservoirs and load macromolecules into space created between nanowires. We show significant increases in loading capacity due to nanowires while retaining adhesion of loaded particles un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Several researchers have fabricated nanowire-coated oral microdevices and used the high surface area of nanowires to effectively load both aqueous and non-aqueous drugs via capillary action. After solvent evaporation, the drug crystallizes over the microdevice surface at the base of the nanowires (Figure 4 D) [71, 72, 74]. Because solvents of drug solutions can evaporate in a manner of minutes with >90% of drug collecting over nanowire-coated microdevices [74], loading via capillary action is efficient in both throughput and minimizing drug waste.…”
Section: Loading Of Novel Micro- and Nanoscale Oral Drug Delivery mentioning
confidence: 99%
“…Several researchers have fabricated nanowire-coated oral microdevices and used the high surface area of nanowires to effectively load both aqueous and non-aqueous drugs via capillary action. After solvent evaporation, the drug crystallizes over the microdevice surface at the base of the nanowires (Figure 4 D) [71, 72, 74]. Because solvents of drug solutions can evaporate in a manner of minutes with >90% of drug collecting over nanowire-coated microdevices [74], loading via capillary action is efficient in both throughput and minimizing drug waste.…”
Section: Loading Of Novel Micro- and Nanoscale Oral Drug Delivery mentioning
confidence: 99%
“…14). These composite particles effectively adhered to microvilli of the epithelial cells of the gastrointestinal tract, 90,91 prolonging the drug retention time and promoting the paracellular transport of small and medium sized drug molecules across the epithelium (Fig. 15).…”
Section: It’s All In a Particle: Drug Delivery Application As An Examplementioning
confidence: 99%
“…Using this approach, researchers have used nanostructured microparticles for increased retention time in oral drug delivery applications. For example, in vitro studies have shown that nanoengineered microparticles, fabricated by growth of silicon nanowires on the surface of glass microbeads, are able to achieve significantly enhanced bioadhesion to a layer of intestinal epithelial (Caco-2) cells in the presence of flow compared with bare microparticles [21,24,25]. …”
Section: Use Of Nanostructured Materials In Overcoming Physiological mentioning
confidence: 99%